Stachytarpheta jamaicensis (L.) Vahl: from traditional usage to pharmacological evidence - Liew, Pearl Majorie; Yong, Yoke Keong (Hindawi Publishing Corporation, 2016)
Introduction: Stachytarpheta jamaicensis (L.) Vahl belongs to the family of Verbenaceae and is commonly known as Gervao, Brazilian tea, verbena cimarrona, rooter comb, or blue porter weed. It is one of the important plants with high medicinal and nutraceutical benefits. S. jamaicensis contains various medicinal properties in traditional and folk medicinal systems, with cures for several diseases. Objective: The objective of this review paper is to collect information concerning the morphology, distribution, traditional usage, phytochemical compositions, biological activities, and safety data of S. jamaicensis. Materials and Methods: The information was obtained from literature search through electronic databases such as PubMed and Google Scholar on S. jamaicensis. Results and Conclusion: The high medicinal properties of this plant, for instance, antimicrobial and antifungal effect as the main activities, but verbascoside as the main active chemical component, make it a valuable source of the medicinal compound. This review paper summarizes all information concerning the morphology, distribution, traditional usage, phytochemical compositions, pharmacological activities, and toxicological studies of S. jamaicensis.